2021
DOI: 10.1021/jacs.1c11277
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Regioselective Control in Aerobic Oxidative C–H/C–H Coupling for C3-Arylation of Benzothiophenes: Toward Structurally Nontraditional OLED Materials

Abstract: The installation of (benzo)thiophene-containing biaryls via coupling reactions has become a staple in designing photoelectric materials. Undeniably, C−H/C−H cross-coupling reactions between two (hetero)aromatics would be a shortcut toward these structural fragments. While more reliable cross-coupling technologies are well-established to provide C2-arylated (benzo)thiophenes, efficient methods that arylate the C3-position remain underdeveloped. Herein we provide insight into the factors that determine regiosele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…In 2021, You, Bin and co-workers presented their investigation of the C3-arylation of benzothiophenes with detailed mechanism experiments and DFT calculations (Scheme 59). 82 It was found that OTf − and OAc − anion play a crucial role in the reaction that X-ray crystallographic analysis showed the key role of OTf − in regioselective dearomatisation and OAc − in base-assisted anti -β-deprotonated rearomatisation.…”
Section: Cross-dehydrogenative Coupling Of Arenesmentioning
confidence: 99%
“…In 2021, You, Bin and co-workers presented their investigation of the C3-arylation of benzothiophenes with detailed mechanism experiments and DFT calculations (Scheme 59). 82 It was found that OTf − and OAc − anion play a crucial role in the reaction that X-ray crystallographic analysis showed the key role of OTf − in regioselective dearomatisation and OAc − in base-assisted anti -β-deprotonated rearomatisation.…”
Section: Cross-dehydrogenative Coupling Of Arenesmentioning
confidence: 99%
“…A handful of studies are available for other types of devices, such as organic light emitting diodes [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], organic solar cells [ 57 , 58 , 59 ], and hybrid DSSC [ 60 ] and perovskite solar cells [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…As Nobel reactions, the Suzuki reaction and Heck reaction have a wide range of applications in organic synthetic chemistry [ 1 , 2 , 3 , 4 ]. The bi-aryl products are multipurpose building blocks in pharmaceuticals, agrochemicals and semiconductor materials such as organic light emitting diodes [ 5 ]. The cross-coupling reaction is one of the most important methods for the direct synthesis of related products [ 6 ].…”
Section: Introductionmentioning
confidence: 99%